Utilization of Statistics in the Evaluation of Guidance and Counseling Services - Yona Apriliana; Daharnis; Rezki Hariko (Journal Of Psychology, Counseling And Education, 2025)
Evaluation of Guidance and Counseling services demands an accurate and objective approach to ensure the effectiveness of the interventions provided. However, the utilization of statistics in the evaluation of BK services is still not optimal, especially in the context of data-based implementation. This study aims to identify and analyze trends in the utilization of statistics in the evaluation of counseling services through a literature review of national and international articles. The method used is a systematic literature review with a descriptive-analytic approach, including identification of the types of statistics used (descriptive and inferential), as well as statistical-based program evaluation techniques. The results showed that the use of statistics greatly contributes to assessing the effectiveness of services, designing needs-based programs, and increasing the accountability of counseling professionals. The conclusions emphasize the need for increased statistical literacy in counselor education as well as the development of evidence-based evaluative instruments. Further research is recommended to test the effectiveness of statistical-based evaluation models at various levels of education.